CONSTITUTIONALITY OF THE CONSTITUTIONAL COURT DECISION NUMBER 90/PUU-XXI/2023 FROM THE PERSPECTIVE OF CONSTITUTIONAL LAW AND FIQH SIYASAH DUSTURIYAH - Febrian Arif Wicaksana; Saipul Nasution; Meutya Amalia; Muhsin Arafat (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The Constitutional Court is a state institution that acts as the Guardian of the Constitution, tasked with providing the right interpretation of the law so that it does not contradict constitutionalism. Decision Number 90/PUU-XXI/2023 issued by the Constitutional Court regarding the age limit for presidential and vice-presidential candidates has caused a lot of controversy starting from determining it until the decision was made. This study aims to analyze the decision of the Constitutional Court Number 90/PUU-XXI/2023, from the perspective of constitutional law and Fiqh Siyasah Dusturiyah (Islamic state politics). The formulation of the research problem is how the constitutionality of the Constitutional Court's decision Number 90/PUU-XXI/2023 and how Fiqh Siyasah Dusturiyah views the constitutionality of the Constitutional Court's decision Number 90/PUU-XXI/2023. The methodology that used in this research is a juridical-normative approach, with a descriptive analysis method. This research relies on literature studies from the primary sources such as court decisions, and laws and secondary sources from books and journals related to Constitutional Law and Fiqh Siyasah Dusturiyah. The results showed that the Constitutional Court's decision Number 90/PUU-XXI/2023 was unconstitutional and this decision is not by the principles of justice and the principle of division of authority in Fiqh Siyasah Dusturiyah. This research showed the importance of fair legal interpretation, maslahat, and compliance with the principles of Fiqh Siyasah Dusturiyah and the constitution in determining constitutional political policy.